"History had taken such a large piece out of my life" — Neuroscientist refugees from Hamburg during National Socialism. Issue 3 (2nd July 2016) - Zeidman, Lawrence A.; von Villiez, Anna; Stellmann, Jan-Patrick; van den Bussche, Hendrik
ABSTRACT: Approximately 9, 000 physicians were uprooted for so-called "racial" or "political" reasons by the Nazi regime and 6, 000 fled Germany. These refugees are often seen as survivors who contributed to a "brain drain" from Germany. About 432 doctors (all specialties, private and academic) were dismissed from the major German city of Hamburg. Of these, 16 were Hamburg University faculty members dismissed from their government-supported positions for "racial" reasons, and, of these, five were neuroscientists. In a critical analysis, not comprehensively done previously, we will demonstrate that the brain drain did not equal a "brain gain." The annihilation of these five neuroscientists' careers under different but similar auspices, their shameful harassment and incarceration, financial expropriation by Nazi ransom techniques, forced migration, and roadblocks once reaching destination countries stalled and set back any hopes of research and quickly continuing once-promising careers. A major continuing challenge is finding ways to repair an open wound and obvious vacuum in the German neuroscience community created by the largely collective persecution of colleagues 80 years ago.